Iowa Birdline update, February 14, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for February 14, 1994. Highlights include a Varied Thrush and a Gyrfalcon. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed